Development of Science Experimental Video: Process of Converting Salt Water to Fresh Water on Classification of Material and Its Change - Annisa Destrina; Arief Muttaqiin (Postgraduate, University of Mataram, 2023)
This study aims to determine the validity and practicality of the video entitled Process of Converting Salt Water to Fresh Water on science subject. In the process of developing this video, STEM elements and critical thinking skills are included. The method used is development research which consists of three stages, namely preliminary research, prototyping stage, and assessment stage. This study used an instrument in the form of a questionnaire in the form of a validity sheet (26 questions), a practical sheet (18 questions), and an interview sheet (5 questions). The validity test was conducted on three education practitioners, while the practicality test was conducted on students at SMPN 2 Padang. The results of the experimental video validity test show very high validity with an average Kappa Momentum (k) value of 0.91. The results of the practicality test through one-to-one evaluation and small group evaluation have a practical value of 91% and 96%, respectively, with a very practical level of practicality. To find out students' interest in the developed video, interviews were carried out which were used as additional data. The results of the interviews obtained student responses to the developed videos, generally students stated that developed videos was very interesting. Also, it is expected that developed videos can help teachers to train students' critical thinking skills.